Shionone Attenuates Sepsis-Induced Acute Kidney Injury by Regulating Macrophage Polarization via the ECM1/STAT5 Pathway - Zhang, Biao; Xue, Yi; Zhao, Jin; Jiang, Huojun; Zhu, Jiaoli; Yin, Hao; Qiu, Yizhen; Hu, Aihao; Xu, Lingqi; Song, Yi; Wang, Xin (Frontiers in Medicine, 2022)
Backgrounds To date, there are no specific drugs approved for the treatment of sepsis associated acute kidney injury (AKI). Shionone is a natural component with anti-inflammatory activity. In this study, we sought to determine the functional role of Shionone in sepsis-induced AKI. Methods Animal models of AKI were constructed by cecum ligation and puncture (CLP) surgery. C57BL/6 mice were randomly assigned to the Sham, CLP, 10 mg/kg DXM, 50 mg/kg Shionone and 100 mg/kg Shionone groups. RAW264.7 treated with lipopolysaccharides (LPS) was used as an in vitro sepsis model and cells were divided into control, LPS, 1 μg/mL Shionone and 2 μg/mL Shionone groups. The pathological status was assessed by Hematoxylin-Eosin (HE) staining assay, protein expressions were detected by immunofluorescence staining and Western blot, macrophage typing was detected by flow, and the levels of pro-inflammatory factors (IL-6, IL-12, IL-1β, TNF-α) and anti-inflammatory factors (IL-10 and TGF-β) were measured using the corresponding kits. Results ECM1 is highly expressed in tissue-infiltrating macrophages under inflammatory conditions. It has been observed that Shionone inhibits the expression of ECM1 and attenuates sepsis-induced injury in kidney and inflammatory factor levels in serum. In addition, Shionone may reduce inflammatory factor levels through the promotion of M2 macrophages by GM-CSF/STAT5/Arg1 pathway to alleviate sepsis induced inflammation in vitro. Conclusion These findings demonstrate that Shionone can alleviate sepsis-induced AKI by promoting M2 macrophage polarization through regulating the ECM1/STAT5 pathway.